Structure of GUN4 from Chlamydomonas reinhardtii. Issue 8 (1st August 2015) - Tarahi Tabrizi, Shabnam; Langley, David B.; Harrop, Stephen J.; Duff, Anthony P.; Willows, Robert D.
<x xml:space="preserve">Abstract</x> The genomes uncoupled 4 (GUN4) protein stimulates chlorophyll biosynthesis by increasing the activity of Mg‐chelatase, the enzyme that inserts magnesium into protoporphyrin IX (PPIX) in the chlorophyll biosynthesis pathway. One of the roles of GUN4 is in binding PPIX and Mg‐PPIX. In eukaryotes, GUN4 also participates in plastid‐to‐nucleus signalling, although the mechanism for this is unclear. Here, the first crystal structure of a eukaryotic GUN4, from Chlamydomonas reinhardtii, is presented. The structure is in broad agreement with those of previously solved cyanobacterial structures. Most interestingly, conformational divergence is restricted to several loops which cover the porphyrin‐binding cleft. The conformational dynamics suggested by this ensemble of structures lend support to the understanding of how GUN4 binds PPIX or Mg‐PPIX.